In fremden Territorien: Delphi, Political Gaming und die subkutane Bedeutung tribaler Wissenskulturen - Dayé, Christian (Österreichische Zeitschrift für Geschichtswissenschaften, 2014)
Delphi and Political Gaming were the first social scientific methods to rely on expert knowledge in order to prognosticate future developments and trends. Both techniques were developed in the early 1950s at the California-based RAND Corporation. Despite this closeness, the epistemic roles of the experts differed greatly. While Delphi views experts as carriers of universal knowledge, political gaming takes a more culturalist and relativist stance towards knowledge. This historical case is used to develop a more sophisticated concept of academic tribes, which focuses on the aspect of descent and emphasizes the continuing relevance of the tribal culture for the scientist’s identity even after leaving the place of academic socialization.